IMPLEMENTASI GAME EDUKASI TEBAK GAMBAR HEWAN UNTUK PENDIDIKAN ANAK USIA DINI - GRESLY RISALDY SERAN DATO; Ida Ayu Putu Febri Imawati; Ni Luh Gede Ambaradewi (Jurnal Manajemen dan Teknologi Informasi, 2022)
One form of entertainment that is familiar and indeed much in demand in our lives is games. Game is an application that is familiar to the community and also early childhood children from all walks of life. However, the development of the game itself is currently still dominated by productions from abroad. In this study the authors chose early childhood children as a sample of game users because considering that children prefer to play games than learn theoretically. From the existing problems, in this study the author built an educational game application so that children can learn while playing. The purpose of this study is to make it easier for children in the learning process in the form of games and with this educational game guessing the picture of animals, it is expected to improve children's abilities in the learning process. The method used in this study is a data collection method consisting of observation, interviews and literature study, for the game making tools used are Evensheet sprites which have been provided with construct 2. While the random data array serves to change the order of questions in the guessing picture educational game application. animal. From the research above, it can be concluded that the application of this animal picture guessing educational game can make it easier for children in the process of learning to recognize animals on this earth and can train children's mindset to be more critical.